Growth in the Middle East and North Africa - Hakura, Dalia (Washington, D.C. : International Monetary Fund, 2004)
This paper analyzes the weak growth performance in the Middle East and North Africa (MENA) region during 1980-2000 using an empirical model of long-run growth. The relative importance of the factors affecting growth is shown to vary across 16 MENA countries. In GCC countries, where oil revenues are significant, large governments appear to have been a key factor stifling private-sector growth and impeding diversification. In other MENA countries poor institutional quality has held back growth. Political instability is also shown to have played a role. While the MENA region's growth differential with east Asia is explained well in the 1980s, this is less so in the 1990s.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet